Coastal Characteristic and Abrasion Hazard in Putri Island, Nongsa, Batam - Undang Hernawan; Nineu Yayu Geurhaneu; Godwin Latuputty (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Putri Island, Nongsa is the outer and frontier island of NKRI region bordering Singapore. Its existence is very important both economically and politically. The management of Putri Island should consider the coastal characteristic that describes character and physical of the beach as the result of interaction between marine influence and coastal condition, geophysical and anthropogenic elements. The purposes of the study are mapping the coastal characteristics as an effort to manage frontier island and describing the abrasion hazard that occurred in this area. The study area is Putri Island, Nongsa. Field survey was conducted in May 2014. Coastal characteristic method wes conducted through geological observation, coastal morphology and coastline character. Bathymetry measurement conducted by echosounder, tidal observation by peilschaal and wind observation by a weather station. The study results show the type of tide is mixed predominantly semi diurnal. The dominant current direction is to the northeastern. The bathymetry conditions between Putri and Batam Island have a depth of up to 20 with a slope of 2.50 and towards the Singapore Strait has a depth of up to 70 m with a slope of > 100. Coastal characteristics of Putri Island is divided into 5 types, ie sandy beaches, mangroves, coral, rocky and cliff. Generally, sandy beaches, mangroves, rocky, rocky have flat morphology and consist of sand, mangroves, coral reefs, gravel and boulder. Low-cliff beaches consist of conglomerates of various materials that are not well consolidated. The abrasion hazard threatens the Putri Island, Nongsa, especially in the north-western part of the island. The abrasion of Putri Island should be managed and performed based on the coastal characteristics of the area.